Teaching business process concepts using enterprise systems in a globalized context - Jaeger, Bjorn; Rudra, Amit; Aitken, Ashley; Chang, Vanessa; Helgheim, B. (IEEE Computer Society, 2010)
There is significant growth in global business operations and ERP systems are deemed as important applications in order to unify and improve fragmented and globalised markets. These systems are complex and students struggle to grasp not only the underlying business concepts but also the technology involved. The paper describes the design and implementation of teaching materials for a multinational cross-company collaboration assignment using a commercial ERP system. It includes elements of 1) integrated business processes, 2) globalization and 3) experiential learning in masters courses at two universities - one in Australia and the other in Norway. We discuss the lessons learned from the pilot study including the development of an evaluation tool, inter-university student communication, evaluation of the learning outcome, and the benefits of the cross-country business role play exercise.